PENGARUH KUALITAS PELAYANAN, KETEPATAN WAKTU PENGIRIMAN DAN FASILITAS TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Pelanggan PT. Pos Indonesia) - Krisna Gusti Putra; Khairul Bahrun (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2023)
This study aims to determine the effect of Service Quality, Timeliness of Delivery and Facilities on Customer Satisfaction of PT. Pos Indonesia (Persero) in Bengkulu City. This study uses quantitative research methods. The population in this study are the customers of PT. Pos Indonesia Kenanga Gardens, Ratu Agung District, Bengkulu City, Bengkulu, with a sampling method using the "Purposive Sampling" method. In the implementation of the study, respondents were obtained randomly, in a total of 98 people. This study uses data collection methods by means of observation, interviews and questionnaires. The data that has been collected will be processed using instrument tests, analysis of respondents' responses, classical assumption test, multiple linear regression analysis, coefficient of determination (R2) and hypothesis testing using SPSS 20. Based on the results of multiple linear regression obtained, the formulation Y = 0.092 +0.101X1 + 0.494X2 + 0.175X3. The coefficient of determination R2 = 0.769 or 76.9% while the remaining 0.231 or 23.1% is influenced by other variables. After the test results have been carried out, it can be seen that the service quality variable (X1) shows tcount of 2.448 > ttable of 1.985 with a significance level of 0.016 ttable of 1.985 with a significance level of 0.00 ttable 1,985 with a significance level of 0.00 < 0.05. The results of the f test show fcount > ftable (108.479 > 2.70) and a significance value of 0.00 < 0.05. From the results of data processing, it can be concluded that the quality of service, timeliness of delivery and facilities partially or simultaneously have a positive and significant effect on customer satisfaction Keyword: service quality, on time delivery, facilities, customer satisfaction